Resistance as a resource for achieving consensus: adjusting advice following competency-based resistance in L2 writing tutorials at a British University. Issue 3 (2nd September 2018) - Leyland, Christopher
Abstract: While a good deal of interaction-based research has examined the delivery of advice, a smaller but very important body of work has shifted focus to consider the ways in which advice is resisted by its recipients in various contexts, including writing tutorials at universities. The current study builds on this research by further investigating the interactional work undertaken from advice being resisted to participants reaching a joint consensus. This Conversation Analytic study draws from a collection of twenty-one one-to-one L2 writing tutorials for international students at a British university. When resisting the tutor's advice, students reveal orientations towards their own levels of competency, providing self-deprecating resistance or high-competence-based resistance. Such responses become a resource for the tutor to diagnose problems and devise solutions better tailored to the needs of the particular recipient. In achieving a joint consensus, tutors rely on strategies such as adapting their initial advice for a less competent student and invoking broader forms of institutionally-preferred behaviours. Finally, this study discusses the importance of students' knowledge and experience and how resistance can prompt the tutor to engage in important pedagogical work and to act as a 'cultural informant'.